Analisis Klaim Al-Ghazali tentang Tindakan Allah dalam 'Al-Iqtisad fi al-I'tiqad': Kajian terhadap Bantahan atas Pemikiran Mu'tazilah - Haya, Haya; Hosaini, Hosaini; Afrita , Juwika; Bustomi, Muhamad Yazid (Progresif : Media Publikasi Ilmiah, 2023)
Imam Al-Ghazali, whose full name is Abu Hamid bin Muhammad bin Ahmad Al-Ghazali, is a prominent figure in Islamic philosophy and theology who was born in 450 AH near Thus, Khurasan, Islamic Republic of Iraq. His important work, "Al-Iqtisad fi al-I'tiqad" (Balance in Belief), provides an in-depth view of Allah's actions, while also being a critical response to Mu'tazilite rationalist thought. This research aims to analyze al-Ghazali's claims regarding Allah's actions and discuss his refutation of Mu'tazilah arguments which emphasize rationality and justice in Divine actions. Al-Ghazali argued that Allah has absolute freedom and his actions are not bound by human understandings of justice and rationality. In contrast, the Mu'tazilites argued that every action of Allah must be in accordance with the principles of justice that can be understood by human reason. This research uses text and context analysis to explore al-Ghazali's argumentative methods and their impact on the theological debates of his time, as well as to understand their relevance in Islamic theological discourse. The results of the research show that according to al-Ghazali, God can burden humans with something they are unable to do, which is different from the Mu'tazilah view which rejects this concept. The Mu'tazilites emphasized that God should not burden humans with something beyond their abilities, because this is considered unfair and destructive. This research provides in-depth insight into al-Ghazali's theological position in defending the doctrine of the Ahlus Sunnah wal Jamaah from the Mu'tazilite rationalist challenge